Spectroscopic Characterization of Stability and Interaction of Pd-Ag Complexes. (7th May 2014) - Lande, Sharad V.; Sharma, Nagesh; Kumar, Ajay; Jasra, Raksh Vir
Abstract : Colloidal metal nanoparticles are of great interest because of their use as catalysts, photocatalysts, adsorbents, and sensors as well as their application in optical, electronic, and magnetic devices. Supported bimetallic systems represent a large part of heterogeneous catalysts which have been used in various reactions important in the chemical, petrochemical, and oil industry. Pd-Ag bimetallic nanocatalysts have become vitally important in some of the petrochemical industry's processes like hydrogenation of C2 –C5 olefins. A heat-treatment method for the preparation of well-stable Pd-Ag complexes is demonstrated using water, concentrated HCl and concentrated nitric acid as media. The stability and interaction of Pd-Ag complexes were characterized by UV-vis absorption spectroscopy. Pd-Ag bimetallic nanoparticles of spherical cubic and octahedral shape in the range of average particle size of 20–60 nm have been prepared and characterized by transmission electron microscopy (TEM).